Connecting to Concrete: Wireless Monitoring of Chloride ions in Concrete structures. (2015) - Abbas, Yawar; ten Have, Bas; Hoekstra, Gerrit I.; Douma, Arjan; de Bruijn, Douwe; Olthuis, Wouter; van den Berg, Albert
Abstract: For the first time, chloride ions are measured wirelessly in concrete. The half-cell potential of a silver/silver chloride (Ag/AgCl) electrode, which corresponds to the concentration of chloride ions, is measured wirelessly. Wireless communication is achieved by an inductive coupling (reflected-impedance) between the coils of the sensor and the readout. The resonance frequency of the sensor coil changes due to the change in the capacitance of a varactor element connected to the Ag/AgCl electrode. The capacitance of the varactor increases with the increase inchloride ion concentration (20 pF/decade). Furthermore, the capacitance can be reliability measured up to a distance of 35 mm between sensor and readout coil. No battery is needed to power the sensor terminal, which makes it feasible to embed it in concrete structures.